Seasonal variation in telomere length of a hibernating rodent - Turbill, Christopher (The Royal Society, 2013)
Small hibernating rodents have greater maximum lifespans and hence appear to age more slowly than similar-sized non-hibernators. We tested for a direct effect of hibernation on somatic maintenance and ageing by measuring seasonal changes in relative telomere length (RTL) in the edible dormouse Glis glis. Average RTL in our population did not change significantly over the hibernation season, and a regression model explaining individual variation in post-hibernation RTL suggested a significant negative effect of the reduction in body mass over the inactive hibernation period (an index of time spent euthermic), supporting the idea that torpor slows ageing. Over the active season, RTL on average decreased in sub-adults but increased in adults, supporting previous findings of greater telomere shortening at younger ages. Telomere length increase might also have been associated with reproduction, which occurred only in adults. Our study reveals how seasonal changes in physiological state influence the progress of life-history traits, such as somatic maintenance and ageing, in a small hibernating rodent.